Surprise!! - Van Lente, Fred (Wolverine. First class., 2010)
The reason Wolverine never tells anybody about his birthday is that every year on that date Sabretooth shows up to dice him into cutlets. Now the love of his life, with whom he is sharing his birthday dinner, is in grave danger!